2011
DOI: 10.1038/ni.1993
|View full text |Cite
|
Sign up to set email alerts
|

Fate mapping of IL-17-producing T cells in inflammatory responses

Abstract: We describe a reporter mouse strain designed to fate-map cells that have activated IL-17A. Here we show that TH17 cells show distinct plasticity in different inflammatory settings. Chronic inflammatory conditions in EAE caused a switch to alternative cytokines in TH17 cells, whereas acute cutaneous infection with Candida albicans, did not result in deviation of TH17 to alternative cytokine production, although IL-17A production was shut off in the course of the infection. During development of EAE, IFN-γ and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

62
1,113
4
15

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,029 publications
(1,194 citation statements)
references
References 52 publications
62
1,113
4
15
Order By: Relevance
“…In addition, pathogenic effector programs within T helper cells may be driven by transcription factors like Stat3 or T-bet, and it may be oversimplified to exclusively allot the expression of these transcription factors to just one T cell subset. For example Th17 cells and even Th2 cells are able to express the Th1 transcription factor T-bet upon sensing particular cytokine cues and only then take on proinflammatory and productive effector functions [153,156].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, pathogenic effector programs within T helper cells may be driven by transcription factors like Stat3 or T-bet, and it may be oversimplified to exclusively allot the expression of these transcription factors to just one T cell subset. For example Th17 cells and even Th2 cells are able to express the Th1 transcription factor T-bet upon sensing particular cytokine cues and only then take on proinflammatory and productive effector functions [153,156].…”
Section: Resultsmentioning
confidence: 99%
“…Although it is now clear that in vitro generated Th17 cells and in vivo generated Th17 cells might be different in terms of developmental plasticity [154], it remains to be determined whether memory T cells that express a classic Th17 phenotype really exist [40]. Using reporter mouse/fate tracking systems, it has been shown that IL-17A or IL-17F producing T cells are reprogrammed to produce both IL-17 and IFN-c or IFN-c only in the spleen and within the CNS [155,156]. Yet, these reprogrammed ''Th17'' cells (even if they do not produce anything else but IFNc) seem to be distinct from classical Th1 cells.…”
Section: Plasticity Of T Helper Cells In Eaementioning
confidence: 99%
“…Another possibility is that Th1 cells may convert to Th17 cells or to an intermediate Th17/Th1 phenotype, which has been previously observed in patients with arthritis and in mice with experimental autoimmune encephalomyelitis (45,46). Regardless of the mechanisms leading to the shift from a primarily IFN␥ response early to a higher Th17/Th1 response later, we nevertheless observed that the frequencies and numbers of IL-17A-and IFN␥-producing CD4ϩ T cells were reduced in the inflamed paws of CXCR6 Ϫ/Ϫ mice compared to arthritic wild-type mice, providing one explanation for the reduced severity of arthritis in CXCR6 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 95%
“…Recent work with fate-mapping knock-in mice showed that IL-17A expression by CD4 + cells can be transient and these so-called ex-Th 17 cells can acquire the ability to express IFNand lose the abi lity to express IL-17A under certain conditions. 7 In the infl amed spinal cords of mice with EAE, T cells expressing IFN-predominantly originated from cells that previously produced IL-17A and this conversion was IL-23-dependent, whereas in an acute cutaneous infection model, T cells making IL-17A neither lose expression of IL-17A nor did these cells acquire expression of other cytokines. 7 DNAse sensitivity studies and global mapping of epigenetic markers of active and closed chromatin help explain the potential for plasticity at the molecular level as the IFN-and Tbx21 loci are poised for expression in Th 17 cells diff erentiated in vitro .…”
Section: Commentaries Nature Publishing Groupmentioning
confidence: 99%
“…7 In the infl amed spinal cords of mice with EAE, T cells expressing IFN-predominantly originated from cells that previously produced IL-17A and this conversion was IL-23-dependent, whereas in an acute cutaneous infection model, T cells making IL-17A neither lose expression of IL-17A nor did these cells acquire expression of other cytokines. 7 DNAse sensitivity studies and global mapping of epigenetic markers of active and closed chromatin help explain the potential for plasticity at the molecular level as the IFN-and Tbx21 loci are poised for expression in Th 17 cells diff erentiated in vitro . 8 It appears then that the local environment and cytokine milieu at sites of infl ammation are key factors in both the development of diff erent types of Th 17 cells and their conversion into distinct subtypes with various levels of pathogenic activity.…”
Section: Commentaries Nature Publishing Groupmentioning
confidence: 99%